AN ANALYSIS OF FIQH JINAYAH AND CRIMINAL LAW ON THE LEGAL PROTECTION FOR CHILDREN AS VICTIMS OF OBSCENITY - Budiman Budiman; Wirani Aisiyah Anwar; A. Rio Makkulau (IAIN Bone, 2022)
The issues raised include the concept of juvenile criminal law from the perspective of fiqh jinayah and positive law, differences in the concept of juvenile crime from the perspective of fiqh jinayah and positive law, the correlation of the concept of juvenile crime to the fiqh perspective and positive law. To study and answer the problem, a multidisciplinary approach is used, namely the normative theological approach (syar'i), juridical/legislative (statue approach), historical (historical approach), sociological (sociological approach), psychology (psychological approach). This research is classified as library research. The results of the study indicate that perpetrators of sexual abuse with child victims, in positive law and fiqh jinayah, sanctions are deterrent so that the perpetrator does not do it again. The laws governing this matter, namely the Republic of Indonesia Law Number 3 of 1997, Law Number 23 of 2002 concerning Child Protection and Law no. 4 of 1979 concerning Child Welfare. In contrast to Islamic law (fiqh), children's perceptions and forms of accountability make criminal acts of children not subject to Uqubah (punishment), but takzir (warning) and ta'dibiyyah (coaching) only. The correlations between the two are: (1) The principle of respect for children. (2) The process of applying punishment for a child who is a criminal act in positive law that is different from a criminal act other than a child. If viewed from the mashlahah rules, giving takzir and ta'dibiyah to children who commit crimes is mashlahah hajiyat (secondary) and mashlahah mulgah.